HIV‐1 ENV gp120 structural determinants for peptide triazole dual receptor site antagonism. Issue 2 (26th October 2012) - Tuzer, Ferit; Madani, Navid; Kamanna, Kantharaju; Zentner, Isaac; LaLonde, Judith; Holmes, Andrew; Upton, Elizabeth; Rajagopal, Srivats; McFadden, Karyn; Contarino, Mark; Sodroski, Joseph; Chaiken, Irwin
Abstract Despite advances in HIV therapy, viral resistance and side‐effects with current drug regimens require targeting new components of the virus. Dual antagonist peptide triazoles (PT) are a novel class of HIV‐1 inhibitors that specifically target the gp120 component of the viral spike and inhibit its interaction with both of its cell surface protein ligands, namely the initial receptor CD4 and the co‐receptor (CCR5/CXCR4), thus preventing viral entry. Following an initial survey of 19 gp120 alanine mutants by ELISA, we screened 11 mutants for their importance in binding to, and inhibition by the PT KR21 using surface plasmon resonance. Key mutants were purified and tested for their effects on the peptide's affinity and its ability to inhibit binding of CD4 and the co‐receptor surrogate mAb 17b. Effects of the mutations on KR21 viral neutralization were measured by single‐round cell infection assays. Two mutations, D474A and T257A, caused large‐scale loss of KR21 binding, as well as losses in both CD4/17b and viral inhibition by KR21. A set of other Ala mutants revealed more moderate losses in direct binding affinity and inhibition sensitivity to KR21. The cluster of sensitive residues defines a PT functional epitope. This site is in a conserved region of gp120 that overlaps the CD4 binding site and is distant from the co‐receptor/17b binding site, suggesting an allosteric mode of inhibition for the latter. The arrangement and sequence conservation of the residues in the functional epitope explain the breadth of antiviral activity, and improve the potential for rational inhibitor development. Proteins 2013. © 2012 Wiley Periodicals, Inc.